Locus of Control, Self-Control, and Health Outcomes - Ferdi Botha; Sarah C. Dahmann (Institute of Labor Economics (IZA), 2022)
We provide the first empirical evidence on the direct link between locus of control and self-control, and how they interact in explaining a range of health outcomes. Using rich Australian survey data, we find that, while the two traits are distinct constructs, a greater internal locus of control is associated with higher self-control. The association between locus of control and health is reduced once we control for self-control, suggesting that self-control mediates at least part of this relationship. Finally, an internal locus of control amplifies the beneficial effects of self-control particularly for physical health.
Keywords: D91; I12; I31; 330; locus of control; self-control; health; health behavior